Developing a contextually relevant ECD milestone guide for South African practitioners - Keren Charge; Linette du Toit; Danielle du Plessis; Tabea Köstlin; Julia Wagner; Renata Eccles; Jeannie van der Linde; Maria du Toit (South African Journal of Childhood Education)
Background: Two hundred and fifty million children under five in low- and middle-income countries are at risk of not achieving their developmental potential. High-quality milestone guides can help mitigate these risks but are often not contextually appropriate for countries like South Africa, because of unavailable resources and its inappropriateness in multilingual group contexts.